2020
DOI: 10.1111/jfb.14328
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterisation of fatty acyl desaturase, Fads2, and elongase, Elovl5, in the Boddart's goggle‐eyed goby Boleophthalmus boddarti (Gobiidae) suggests an incapacity for long‐chain polyunsaturated fatty acid biosynthesis

Abstract: The biosynthesis of long-chain polyunsaturated fatty acids (LC-PUFA), a process to convert C18 polyunsaturated fatty acids into eicosapentaenoic acid (EPA), docosahexaenoic acid (DHA) or arachidonic acid (ARA), requires the concerted activities of two enzymes, the fatty acyl desaturase (Fads) and elongase (Elovl). This study highlights the cloning, functional characterisation and tissue expression pattern of a Fads and an Elovl from the Boddart's goggle-eyed goby (Boleophthalmus boddarti), a mudskipper species… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Fatty acid synthase (FASN) is an important rate-limiting enzyme that catalyzes the synthesis of fatty acids used for energy generation, extended with C2 units derived from the elongation substrate malonyl-CoA [37]. The biosynthesis of long-chain polyunsaturated fatty acids requires the concerted activities of fatty acyl desaturase (FADS) and elongase (ELOVL) [38]. Similarly, Zheng et al [18] found significant up-regulation of FAS, ELOVL1, ELOVL5, and ELOVL6 expression in a new backcross of T. gigas ♀× (T. gigas ♀× Bleak ♂) ♂, the growth advantage of this backcross may be related to the increased fatty acid synthesis.…”
Section: Analysis Of Candidate Degs Involved In Fatty Acid Metabolismmentioning
confidence: 99%
“…Fatty acid synthase (FASN) is an important rate-limiting enzyme that catalyzes the synthesis of fatty acids used for energy generation, extended with C2 units derived from the elongation substrate malonyl-CoA [37]. The biosynthesis of long-chain polyunsaturated fatty acids requires the concerted activities of fatty acyl desaturase (FADS) and elongase (ELOVL) [38]. Similarly, Zheng et al [18] found significant up-regulation of FAS, ELOVL1, ELOVL5, and ELOVL6 expression in a new backcross of T. gigas ♀× (T. gigas ♀× Bleak ♂) ♂, the growth advantage of this backcross may be related to the increased fatty acid synthesis.…”
Section: Analysis Of Candidate Degs Involved In Fatty Acid Metabolismmentioning
confidence: 99%
“…The resulting pYES2-elovl1 and pYES2-elovl6 constructs were subsequently transformed into Saccharomyces cerevisiae yeast competent cells (INVSc1, Thermo Fisher Scientific, MA, USA) using Frozen-EZ yeast transformation II kit (Zymo Research, CA, USA) and plated on uracil deficient YPD agar plate and confirmed with PCR-based screening. To characterise the MUFA and PUFA elongation capacity of both Elovl enzymes, a single colony from the recombinant yeast was selected, and propagated with the culture medium as described previously (Soo et al, 2020). Transgenic yeast expressing each of the G. lalandii Elovl were grown in the presence of exogenously added MUFA (16:1n-7 and 18:1n-9) or PUFA (ALA,LA,EPA,ARA,and DHA) substrates.…”
Section: Functional Characterisation Of Elovl1 and Elovl6mentioning
confidence: 99%
“…The poly-unsaturated fatty acids (PUFAs) are involved in numerous critical biological processes [ 1 , 2 , 3 ]. Fish is an important PUFA source for human diet and is essential for human health [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%